Pemberian Diet Tinggi Energi dan Tinggi Protein pada Pasien dengan Penyakit Kolelitiasis Pasca Operasi Kolesistektomi: Sebuah Laporan Kasus - Kayla Lalintang Ramadhina; Farapti Farapti (Media Gizi Kesmas, 2024)
Background: Cholelithiasis is a stone that forms in the gallbladder which is composed of cholesterol, bilirubin, and bile. The presence of risk factors such as obesity, genes, female gender, lifestyle (often eating fatty foods), pregnancy, certain medications (estrogens, fibrates, somatostatin analogues), gallbladder stasis, metabolic syndrome, extreme diets, prolonged fasting, and bariatric surgery may increase the occurrence of cholelithiasis. Cholelithiasis can be treated with laparoscopic cholecystectomy. The standardized Nutrition Care Process (NCP) is carried out by providing a high-energy and high-protein diet. Objective: To determine the management of standardized NCP for patients with a high energy and high protein diet for cholelithiasis post-cholecystectomy surgery. Methods: The case study was carried out directly (using primary data) which was conducted in September 2023 on patient at RS X Surabaya Results: After monitoring and evaluation for three days, the results showed that the patient’s nutritional intake fluctuated and had not yet met the target (90 – 110%) of daily requirements, but had met 50% of daily requirements. This occured because the patient remains in the Ebb Phase and Flow Phase following surgery, accompanied by nausea and stomach discomfort, which has reduced the patient’s appetite. On the contrary, the physical/clinical examination of patient is increasing daily. The anthropometry results also showed that there was no weight loss. The laboratory result was not reexamined as it is categorized as normal. Conclusion: The observed patient’s recovery is not progressing well, as the results of monitoring nutritional intake still show fluctuating changes. However, the physical/clinical results show an improvement. Physical/clinical examination of the pain experienced by the patient gradually improved but had not fully recovered. The anthropometric also met the target; there was no significant weight loss. The laboratory result was not reexamined as it is categorized as normal. Overall, the nutritional intervention provided reached 50% of the recommended daily requirements.